Economic impact of sole and biennial turmeric cultivation with mango and litchi as an intercrop - Saran, P.L.; Singh, K.; Devi, G. (Annals of Agricultural Research, 2016)
An intercropping trial was conducted at twenty five farmers' field during 2011-2012 under agroclimaticconditions of North Eastern Plains Zone. The five combinations of different cropswith turmeric were grown. The higher yield per plant (0.235 kg + 0.002 kg), yield per hectare(352 + 38 q/ha) and maximum rhizome diameter in turmeric (6.6 cm) was observed with biennialturmeric + wheat which were significantly better as other intercrops. The highest average grossreturn (` 241000), net return (` 99177), B: C ratio (1.70) and cost of production (` 6.25/kg) wereobserved in turmeric + litchi, followed by biennial turmeric + wheat and turmeric + mango croppingsystems.